SOCIOLOGY AS A TOOL OF “PEDAGOGICAL INTELLIGENCE” - A. L. Andreev (Высшее образование в России)
The article addresses the issues concerning the development of the humanitarian component of higher education in Russia. The main idea of the article is that for modern Humanities education it is of fundamental importance to strengthen its functional links with promising social changes and social practices. In this connection, the need for compulsory systematic sociological support of the educational process increases: sociological research acts as a kind of “pedagogical intelligence” tool, with the help of which the parameters of a meaningful adjustment of the Humanities education are identified and its final social efficiency is diagnosed. This thesis is illustrated by the example of such a mandatory discipline studied at Russian higher school as History. The article describes the current socio-cultural situation in the study and teaching of History, which is aggravated not only due to a decrease in the level of historical competence of young people, but also owing to the divergence of historical discourses, as well as to some postmodernist methodological principles that hamper the establishment of historical truth. The article discusses the influence of this situation on the perception of the scientific concepts of the historical process, which constitute the content basis of the educational process, on the course of this process and its results. In this regard, the role of sociological methods for the identification of real historical self-consciousness is noted, allowing to take into account the state of the social environment and to “adjust” historical education to the needs of the developing society. The author substantiates the idea of transition to flexible, selfcorrecting curricula, which, thanks to the use of sociological support, is able to react quickly to deep socio-cultural trends of various types. The argument given in support of this point of view uses data obtained in the course of sociological surveys conducted at various times in leading Russian universities. In conclusion, the content and organizational-methodological aspects of modernizing History teaching are examined in accordance with the considerations expressed in the article. In this regard, a desire was expressed for more coordinated training programs on Humanities disciplines.